Formation of large low shear velocity provinces through the decomposition of oxidized mantle - Wenzhong Wang (Nature Portfolio, 2021)
Dense Fe3+-rich bridgmanite can explain the seismic features of Large Low Shear Velocity Provinces, as it can form large-scale thermochemical piles in the deep mantle that remain stable throughout Earth’s history.